Nasal coda neutralization in Shanghai Mandarin: Articulatory and perceptual evidence. Issue 1 (2nd December 2020) - Faytak, Matthew; Liu, Suyuan; Sundara, Megha
Shanghai Mandarin is reported to neutralize /n/ and /ŋ/ after non-low vowels, a change also reported for other varieties of Chinese. However, the place of articulation of the resulting nasal is unclear. We used production and perception experiments to determine the contexts which condition neutralization and the place of articulation of the resulting nasal. Analysis of ultrasound data using a dimensionality reduction technique revealed that neutralization in production was dependent on the height of the preceding vowel: The highest vowel /i/ conditioned a consistent, non-structure-preserving neutralization to a fronted velar or palatal nasal; the mid vowel /ə/ conditioned an inconsistent, structure-preserving neutralization to [n]; and no neutralization occurred after the low vowel /a/. In contrast, Standard Mandarin controls produced the contrast in all vowel contexts. A follow-up perception experiment confirmed that, consistent with complete neutralization, Shanghai Mandarin listeners failed to distinguish alveolar and velar nasals following /i/. More surprisingly, so did Standard Mandarin listeners, suggesting a near merger of the nasal codas following /i/ in Standard Mandarin. Our results provide support for a role for substantive factors in neutralization-driven sound changes.